"O Último Minuto": reflecting on coach identity and role prominence in contemporary football. Issue 1 (2nd January 2021) - De Sa Fardilha, Francisco; Allen, Justine B.
ABSTRACT: Literary fiction has been recognised as a vehicle of cultural transmission that can be used to reflect on real issues. If used as data sources, sports novels may be useful for making sense of the complexity and messiness of the coaching process. Drawing upon the reading of "O Último Minuto", written by Brazilian author Marcelo Backes, this paper uses the trajectory, experiences, and emotions of its protagonist – João Iánic -, as a springboard to reflect on the challenges of coach identity and role prominence in contemporary sport and society. Although role prominence may enhance coaches' commitment, energy and motivation to invest in their tasks, strong coaching identity may as well have its potential pitfalls. If other identities are dismissed, and the coaching identity is threatened (e.g. by the increasing commercialisation of sport, especially football) there is the risk of a negative path, which can result in experiences of burnout, unsustainable pressure, and ill-being. More research is needed to uncover the mechanisms that lead to or create the "turning points" in the coaches' paths. A better understanding of identity prominence may also assist with promoting its facilitative nature while mitigating its potentially debilitative consequences.